Reasons for choosing test – operation setting for vibro - acoustical method of test-operation concrete poles in the overhead system - Kuznetsov, V. H.; Poliakh, O. M. (Science and Transport Progress, 2011)
The scientific substantiation of a selection of diagnostic parameter for a new method of diagnostics of ferroconcrete supports of an electric-traction network on the basis of the average information on a support condition is conducted.